Oxygen permselectivities through supramolecular polymer membranes prepared by highly selective photocyclic aromatization of poly(substituted acetylene). (3rd October 2017) - Yin, Guanwu; Ohtaka, Eri; Aoki, Toshiki; Wang, Jianjun; Teraguchi, Masahiro; Kaneko, Takashi
Abstract: In order to estimate oxygen permselectivities through a supramolecular polymer membrane for the first time, we prepared three kinds of composite membranes consisting of a supramolecular polymer membrane and a conventional organic polymer membrane. Supramolecular polymer membranes were prepared by using highly selective photocyclic aromatization of poly(substituted acetylene)s. It was found that the supramolecular polymer membrane had oxygen permselectivity (α = P O 2 / P N 2 ) around three in spite of its low molecular weight. Graphical abstract: Highlights: Three new composite membranes consisting of a supramolecular polymer membrane having enough strengths have been prepared. These composite membranes have been prepared by highly selective photocyclic aromatization we had developed before. The supramolecular polymer membranes were found to have an ability to separate oxygen and nitrogen in permeation. The permselectivities were relatively high and similar to those for usual organic polymer membranes. To the best of our knowledge, this is the first experimental result on gas separation by supramolecular polymer membranes.